2017
DOI: 10.1021/acs.macromol.7b00857
|View full text |Cite
|
Sign up to set email alerts
|

Single-Material Organic Solar Cells Based on Electrospun Fullerene-Grafted Polythiophene Nanofibers

Abstract: Highly efficient single-material organic solar cells (SMOCs) based on fullerene-grafted polythiophenes were fabricated by incorporating electrospun one-dimensional (1D) nanostructures obtained from polymer chain stretching. Poly(3-alkylthiophene) chains were chemically tailored in order to reduce the side effects of charge recombination which severely affected SMOC photovoltaic performance. This enabled us to synthesize a donor− acceptor conjugated copolymer with high solubility, molecular weight, regioregular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
94
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(94 citation statements)
references
References 42 publications
0
94
0
Order By: Relevance
“…[71] As in their previous report, the final fixation of C 60 was quantitatively achieved by click chemistry. [65] Stability tests in ambient conditions have shown that this cell still presents a PCE of 4.62% after 42 days of storage. A significant fluorescence quenching of P3HT was observed for diluted solutions of the copolymers, while this phenomenon was not observed for mixtures of the two components at similar concentrations of P3HT.…”
Section: "Double-cable" Polymers With Fullerene Acceptor Groupsmentioning
confidence: 92%
See 1 more Smart Citation
“…[71] As in their previous report, the final fixation of C 60 was quantitatively achieved by click chemistry. [65] Stability tests in ambient conditions have shown that this cell still presents a PCE of 4.62% after 42 days of storage. A significant fluorescence quenching of P3HT was observed for diluted solutions of the copolymers, while this phenomenon was not observed for mixtures of the two components at similar concentrations of P3HT.…”
Section: "Double-cable" Polymers With Fullerene Acceptor Groupsmentioning
confidence: 92%
“…After thermal annealing at 130 °C, a SMOSC based on copolymer 3 delivered a J sc of 6.15 mA cm −2 , a V oc of 0. [65] A copolymer of 3-dodecylthiophene and 3-(bromohexylthiophene) was synthesized by Grignard metathesis (GRIM) followed by nickel-catalyzed polymerization. [70] In further investigations of the synthesis and structure of the diblock copolymers, the same authors have synthesized P3HT-based diblock copolymers with controllable block lengths by combining Grignard metathesis and nickel-catalyzed quasiliving polymerization.…”
Section: "Double-cable" Polymers With Fullerene Acceptor Groupsmentioning
confidence: 99%
“…[20][21][22][23][24][25][26] Fullerene derivatives were regarded as a promising electronic transport layer (ETL) material due to their distinguished advantages of high electron mobility and good energy level matching with the active layers of OSCs. [27][28][29][30][31] The polarities of the fullerene derivatives were influenced significantly by the presence of functional groups, such as sulfonate, ether chain, ester, and carboxylic acid [32][33][34][35] A few fullerene derivatives with functionalized anchoring groups have been developed as a modification layer of metal oxide in inverted OSCs. [36][37][38] They can be easily processed through a solution-based method, which demonstrated good compatibility between organic active layer and metal oxide.…”
Section: Doi: 101002/macp201800477mentioning
confidence: 99%
“…fabricated the photovoltaic devices using the electrospun fibers and investigated the influences of fiber morphology and relative humidity during electrospinning process on the performance of systems. Very recently, highly efficient single‐material organic solar cells based on fullerene‐grafted polythiophenes were also developed through applying the electrospun one‐dimensional nanostructures acquired on the basis of polymer chain stretching . In the current work, the settled/unsettled nanofibers blended from PBDT‐DTNT, PBDT‐DTNT/grafted‐rGO, and grafted‐rGO were prepared via electrospinning technique.…”
Section: Introductionmentioning
confidence: 99%